2016
DOI: 10.1371/journal.pone.0156071
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Bile Salt-Stimulated Lipase in Preterm Infant Feeding: A Randomized Phase 3 Study

Abstract: IntroductionFeeding strategies are critical for healthy growth in preterm infants. Bile salt-stimulated lipase (BSSL), present in human milk, is important for fat digestion and absorption but is inactivated during pasteurization and absent in formula. This study evaluated if recombinant human BSSL (rhBSSL) improves growth in preterm infants when added to formula or pasteurized breast milk.Patients and MethodsLAIF (Lipase Added to Infant Feeding) was a randomized, double-blind, placebo-controlled phase 3 study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Bile salt stimulated lipase, present in human milk, which would improve the digestibility of long-chain fatty acids. In a multi-center randomized trial, recombinant BSSL has been tested vs. placebo with a follow-up for 12 months; there was no improvement in weight growth in preterm infants except in the sub-group of Small for Gestational Age infants but with some imbalance in the adverse effects ( 79 ).…”
Section: A Biomarker In Breast Milk Does Not Necessarily Mean a Bioacmentioning
confidence: 99%
“…Bile salt stimulated lipase, present in human milk, which would improve the digestibility of long-chain fatty acids. In a multi-center randomized trial, recombinant BSSL has been tested vs. placebo with a follow-up for 12 months; there was no improvement in weight growth in preterm infants except in the sub-group of Small for Gestational Age infants but with some imbalance in the adverse effects ( 79 ).…”
Section: A Biomarker In Breast Milk Does Not Necessarily Mean a Bioacmentioning
confidence: 99%
“…In fact, results of a randomized clinical trial in preterm infants using a crossover design indicate that the addition of recombinant human BSSL vs. placebo to the infant feed (pasteurized human milk or infant formula) improves growth velocity and long chain polyunsaturated fatty acid absorption [ 42 ]. A subsequent multi-center study using a parallel study design enrolling 415 preterm infants confirmed a beneficial effect on growth for small-for-gestational-age infants, but not for the full study population including appropriate-for gestational age infants [ 48 ]. For mothers who produce 2-fucosylated glycans (secretor mothers), it could be shown in vitro that BSSL acts as a decoy receptor for human calicivirus strains and may provide some protection from gastroenteritis due to norovirus infection in breast-fed infants [ 43 ].…”
Section: Human Milk Proteins With Bioactivitymentioning
confidence: 99%
“…The effect of recombinant human bile salt-stimulated lipase (rhBSSL) was investigated by Casper et al [ 37 ]. BSSL is a lipolytic enzyme facilitating digestion and absorption of fat in human milk and formula.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of rhBSSL to formula or donor human milk did not result in a higher growth velocity in a phase 3 study [ 37 ]. This result is in contrast with the phase 2 study, which had a cross-over design with a washout period of 2 days ( n = 65 in total) [ 62 ].…”
Section: Discussionmentioning
confidence: 99%